In silico analysis of V48A dihydropteroate synthase mutation to dapsone on Mycobacterium leprae from Papua - Yustinus Maladan; Hana Krismawati; Hotma Martogi Laurensia Hutapea; Antonius Oktavian (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2020)
Latar belakang: Lepra merupakan penyakit yang disebabkan oleh Mycobacterium leprae. Resistensi obat merupakan salah satu tantangan dalam pemberantasan kusta khususnya di Papua. Adanya mutasi pada gen folP1 penyandi dihydropteroate synthase (DHPS) merupakan dasar untuk deteksi molekuler resistensi dapson pada penyakit lepra. Tujuan penelitian ini adalah mendeteksi mutasi pada gen folP1 Mycobacterium leprae dari Papua, Indonesia dan menganalisis pengaruh mutasi tersebut terhadap dapson dengan metode in silico. Metode: Identifikasi mutasi pada gen folp1 M. leprae dilakukan melalui proses Basic Local Alignment Search Tool (BLAST) di gene bank. Analisis efek mutasi dengan menggunakan server Have (y) Our Protein Explained (HOPE). Prediksi binding pocket menggunakan Computed Atlas of Surface Topography of proteins (CASTp). Homologi modeling struktur 3D DHPS menggunakan server Iterative Threading ASSEmbly Refinement (I TASSER). Analisis docking dengan menggunakan AutoDock Vina yang terintegrasi dengan aplikasi Python Prescription (PyRx). Hasil: Hasil sekuensing menunjukkan adanya variasi dalam gen folP1 M. leprae yaitu perubahan dari Timin (T) menjadi Sitosin (C) pada nukleotida 143. Residu yang bermutasi (V48A) terletak pada domain yang penting untuk aktivitas protein dan kontak dengan residu di domain lain. Ada kemungkinan bahwa interaksi ini penting untuk fungsi protein secara benar. Mutan V48A tidak banyak mempengaruhi stabilitas dari dihydropteroate synthase M. leprae. Kesimpulan: Berdasarkan analisis molecular docking, mutasi V48A tidak mempengaruhi binding affinity dapson terhadap dihydropteroate synthase M. leprae. Hasil ini menunjukkan mutan V48A kemungkinan tetaprentan terhadap dapson. Dengan demikian perlu dilakukan uji in vivo untuk mengkofirmasi efek mutasi V48A. Kata kunci: Mycobacterium leprae, folP1 gene, dihydropteroate synthase, dapson Abstract Background: Leprosy is a disease caused by Mycobacterium leprae. Drug resistance is one of the challenges in leprosy elimination especially in Papua. The presence of mutations in folP1 gene that encode dihydropteroate synthase (DHPS) was considered as the exclusive basis for molecular detection of dapsone resistance in leprosy. The objective of this study was to detect mutations in the folP1 gene of Mycobacterium leprae from Papua, Indonesia and to analyze the effect of these mutations on dapsone using the in-silico method. Methods: Identification of mutations in the folp1 M. leprae gene is carried out through the Basic Local Alignment Search Tool (BLAST) process in the gene bank. The analysis of the effects of mutations using the Have (y)Our Protein Explained (HOPE) server. Bindings pocket prediction is done using the Computed Atlas of Surface Topography of proteins (CASTp). Homology modeling 3D structure of DHPS using the Iterative Threading ASSEmbly Refinement (I-TASSER) server. Docking analysis was performed using AutoDock Vina which is integrated with the Python Prescription (PyRx) application. Results: The sequencing results showed a variation in the folP1 M. leprae gene, namely a change from thymine (T) to cytosine (C) in nucleotide 143. The mutated residue (V48A) is in a domain that is essential for the activity of the protein and in contact with residues in another domain. It is possible that this interaction is important for the correct function of the protein. V48A mutants did not significantly affect the stability of DHPS M. leprae. Conclusion: Based on molecular docking analysis, this mutation does not affect binding affinity dapsone against M. leprae dihydropteroate synthase. These results indicate that the V48A mutant is likely to remain susceptible to dapsone. Thus, it is necessary to do an in vivo test to confirm the effect of the V48A mutation. Keywords: Mycobacterium leprae, folP1 gene, dihydropteroate synthase, dapsone